“I search for information and I don’t stop until I get it” Online information search and language choice of Greenlandic and Icelandic youth - Jakob Beat Altmann 1996- (2022)
The research was performed in cooperation with Ilisimatusarfik (University of Greenland). The goal of this research is to identify and analyze the factors that play an influential role in the language selection process of Greenlandic and Icelandic youth in their search for information online. That is to say, the reasons and processes that make the information searcher decide which language to use and apply in their online search. As both places (Greenland and Iceland) were colonies of Denmark, this analysis will be set in a postcolonial frame in order to understand the underlying power dynamics in the language contact and information accessibility online. The researched population are high shool students in the capitals of Iceland (Reykjavík) and Greenland (Nuuk). Questionaires were distributed in the high schools with both multiple choice, Likert scale and free text answers.The answers were analyzed with a focus on the information search behavior online and the students‘ identification with language. It was found that while Icelandic has a relatively safe stance online, it is in constant opposition with English in the perception of Icelandic youth. Greenlandic is only used for the acquisition of local information and does not stand in direct opposition with English. For Greenlandic youth, it is rather Danish that shares the same functionality with English. Danish, on the other hand, is negligible in the information search behavior online of Icelandic youth. It was proposed to support Icelandic and Greenlandic in their online performance by further developing natural language processing tools for those languages and enlarging work on the Semantic Web.